The effects of P-hydroxycinnamic acid in ameliorating spatial learning and flexibility deficits in rats with chronic cerebral hypoperfusion - Natsuda Manyagasa; Wachiryah Thong-asa (Penerbit Universiti Kebangsaan Malaysia, 2019)
Cerebral blood reduction resulting in oligemic energy failure and metabolic insufficiency initiates gradual neurodegeneration and cognitive impairments. We investigated the neuroprotective effects of p-hydroxycinnamic acid (pHCA) on neurodegeneration in association with cognitive impairments in rats with chronic cerebral hypoperfusion (CCH). Forty male Sprague-Dawley rats were randomly divided into 4 groups: Sham-veh, 2VO-veh, 2VO-pHCA50 and 2VO-pHCA100. We used modified 2-vessel occlusion (2VO) to induce CCH, and the 2 latter groups were given 50 mg/kg and 100 mg/kg of pHCA after the 2VO operation, respectively, which continued for 3 weeks. The behavioral tests consisted of anxiety-like behavior tested in an elevated plus maze (EPM) and hippocampal-dependent spatial learning and flexibility tested in a Morris water maze (MWM). Brain oxidative status, infarction, vulnerable hippocampus and corpus callosum (CC) white matter degeneration were evaluated. The results showed that modified 2VO induced reversible short-term anxiolytic-like behavior in the EPM (p < 0.05). Brain tissue analysis showed that modified 2VO induced gradual change to brain oxidative status (p > 0.05) with significance infarction, vulnerable hippocampal CA1, CA3, DG and CC degeneration (p < 0.05). These were found along with significant spatial learning and flexibility deficits (p < 0.05). Additionally, 100 mg/kg of pHCA significantly ameliorated the spatial learning and flexibility deficits, which coincided with the significant decreases of infarction volume, CA1, CA3 and CC degeneration (p < 0.05). We conclude that pHCA’s improving effects on spatial learning and flexibility deficits are neuroprotective against oligemic energy failure-induced vulnerable neuronal and white matter degeneration in CCH rats.